2014
DOI: 10.1080/02615479.2014.937415
|View full text |Cite
|
Sign up to set email alerts
|

A Case-based Collaborative Learning Model for Teaching Advocacy

Abstract: Social work graduate school programs focusing on clinical practice have traditionally attended less to the profession's advocacy role. Masters-level clinical social work students, therefore, may not receive adequate training to understand their roles in advocating for or against policies that directly impact their practice. This article proposes a collaborative learning model called 'Advocacy Week', which prepares students for a statewide NASWsponsored Advocacy Day. Using case presentations prepared in collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Here again, the students who participated in most of the evaluated activities were not necessarily only those in macro tracks or concentrations, but were also in direct or clinical practice (e.g. Saulnier, ; Kilbane, Rodriquez Freire, Young, Hong, & Pryce, ) or BSW students (e.g. Zubrzycki & McArthur, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here again, the students who participated in most of the evaluated activities were not necessarily only those in macro tracks or concentrations, but were also in direct or clinical practice (e.g. Saulnier, ; Kilbane, Rodriquez Freire, Young, Hong, & Pryce, ) or BSW students (e.g. Zubrzycki & McArthur, ).…”
Section: Resultsmentioning
confidence: 99%
“…These focus on an internet‐based PP assignment (Tower & Hartnett, ), observing parliamentary proceedings (Henman, ), a hypothetical exercise of designing a policy which requires students to define its objectives, design strategies for achieving them and compare their costs and benefits (Weaver & Nackerud, ), or studying a compelling social problem in the news (antecedents, complexity, impact on different populations), understanding existing policies, and formulating potential solutions (Sherraden, Guo, & Umbertino, ). The fifth study evaluates the incorporation of a Case‐Based Learning workshop that creates concrete contexts in which policy and clinical practice impact on one another, into the Advocacy Week Model (Kilbane et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This event is an opportunity for students to practice classroom learned skills by traveling to their state capitol and engaging with policymakers on specific legislative issues (Lane et al, 2012). Some states have extended Advocacy Day into a week-long lobbying experience, in partnership with academic faculty, state legislators, and local NASW chapters to promote cross-collaborative advocacy efforts (Beimers, 2016;DeRigne et al, 2014;Kilbane, Pryce, Young, & Hong, 2013;Kilbane, Rodriquez Freire, Young, Hong, & Pryce, 2014;Kilbane & Freire, 2013).…”
Section: Applied Practice and Engagementmentioning
confidence: 99%
“…Findings suggest that formal training and understanding of the complexities of advocacy and policy are important to the actual practice of it. Kilbane et al (2014) reported that "the degree to which [social workers] perceive advocacy as at least professionally a relevant matter to them, if not taking it to be their own practice, is highly associated with understanding the importance and relevance of advocacy to social work practice" (p. 1064). In other words, when people believe that policy and advocacy is relevant to them personally, they also tend to believe that it is relevant to their practice/profession.…”
Section: Self-of-the-advocatementioning
confidence: 99%